CoFlame Sebagai Inovasi Energi Terbarukan: Kajian Sistematis Dan Analisis Kelayakan Bisnis Pemanfaatan Limbah Kopi - Ammar Faqih Zulkarnain; Suci Purnama; Bella Nafisa Muherli; Putri Afridayanti; Alfi Rahmatillah; Irfan Zikri (Departemen Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala associated with AAI (Asosiasi Agribisnis Indonesia). Jl. Tgk. Hasan Krueng Kalee No. 3, Kopelma Darussalam, Banda Aceh, 23111, Indonesia. Email: agrisep@usk.ac.id, 2026)
The growing energy demand in Indonesia, driven by population growth and industrial expansion, necessitates the development of sustainable alternative energy sources. One promising opportunity lies in transforming coffee waste into bio-briquettes through the CoFlame innovation. This study aims to examine the technical, environmental, socio-economic, and business feasibility aspects of utilizing spent coffee grounds as renewable energy. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines, involving a search of 50 peer-reviewed articles from Garuda Ristekbrin, SINTA, and Google Scholar databases. After screening and selection, nine core studies were identified and analyzed thematically. The findings indicate that coffee grounds exhibit competitive physical and chemical characteristics, low moisture and ash content, and high combustion stability. Environmentally, the utilization of coffee waste reduces organic waste accumulation, carbon emissions, and pollution while promoting circular economy practices and community empowerment. Financially, the CoFlame model demonstrates strong profitability and confirming its economic feasibility. This study concludes that CoFlame represents a sustainable, inclusive, and profitable renewable energy innovation, contributing to the achievement of SDGs 7, 8, 9, 12, and 13. Academically, the research enriches literature on biomass-based renewable energy and circular economy, while practically, it offers insights for developing inclusive green business models based on agricultural waste in Indonesia.